Allyl isothiocyanate attenuates LED light-induced retinal damage in rats: exploration for the potential molecular mechanisms - Orhan, Cemal; Gencoglu, Hasan; Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Morde, Abhijeet Ashok; Şahin, Kazım (Taylor & Francis Ltd, 2021)
Purpose Environmental light pollution due to artificial light may increase the rate and severity of retinal diseases, and plant-based nutritional interventions with antioxidant properties have the potential to reverse this phenomenon. We aimed to investigate the potential effects of allyl isothiocyanate (AITC) against white light-emitting diode (LED)-induced retinal degeneration (RD) in the rats. Methods Twenty-eight male rats were allocated as: (i) Control, (ii) LED, (iii) LED + AITC (10 mg/kg BW), (iv) LED + AITC (20 mg/kg BW). Rats were administered with AITC for 28 days, followed by two days of intense environmental LED light (750 Lux) exposure to the eyes. Animals were sacrificed immediately at the end of the study, then the blood and eyeballs were taken for the biochemical, western blotting, and histopathology examinations. Results AITC lowered the serum and retina malondialdehyde (MDA) levels while significantly (p < 0.05) improving the retinal antioxidant enzyme activities in a dose-dependent manner. AITC improved retinal and outer nuclear layer (ONL) thickness as compared to the LED group (p < 0.05). AITC increased the levels of Bax, caspase-3, HO-1, GAP43, and VEGF, while decreasing IL-1 beta, IL-6, NF-kappa B, Bcl-2, GFAP, Grp78, activating ATF4 and ATF6 as compared to the LED group (p < 0.05). Conclusion In conclusion, four weeks of AITC administration to the rats showed specific protective effects against two days of intense LED light-induced retinal damage; through antiinflammatory, antioxidant, anti-apoptotic, and modulating mitochondrial metabolic pathways.
Keywords: Allyl isothiocyanate; light stress; oxidative stress; rat retina